(untitled) (Eurasian Journal of Philology Science and Education, 2022)
In the article, we will try to consider the extralinguistic nature of clothing names found in the language of M. Auezov’s dramas in unity with National Knowledge. The aim of the article is to show spiritual and material culture of the people through the works of M.Auezov. Brief description of the scientific and practical significance of the work. In general prose and poetic works, the function of vestems in a sentence is clearly visible. And, vestems in dramatic works are often mentioned in scenes. Therefore, it is up to the researcher to determine what function it performs. For example, when Karagoz is going to get married she wears saukele. It was written by the author, and the spectator is watching, and our goal is to find out the purpose of putting it on. Brief description of the research methodology. While studying the material, we used the method of semantic and stylistic analysis of the vocabulary of a work of art, etymological analysis, supplemented by the method of motivational and comparative analysis, descriptive method, component analysis. The main results and analysis, conclusions of the research. From the point of view of modern perception, tokens representing clothing can be divided into the following groups: 1) familiar words; 2) words that are familiar, but do not correspond to the concept of» clothing»; 3_ familiar but less common words in the modern Kazakh language; It requires the ratio of active and passive vocabulary in the vocabulary of the modern reader in the language of M. Auezov, the replacement of unfamiliar lexemes into semantically developed lexical units, which primarily contributes to the formation of lexicographic competence of the linguistic personality. Practical significance of the results of the work. The results of this study are widely used in linguocultural studies, cognitive linguistics, linguistic analysis of literary texts. Key words: linguoculturemes, saukele, national culture, information, material culture, expressive qualities7